Implikasi Aliran Filsafat Pragmatisme Terhadap Praksis Pendidikan - Priyanto, Dwi (Jurnal Pendidikan Islam Indonesia, 2017)
This papers aims to describe of implication ideology pragmatic philosophy toward practical in education. Conception of pragmatic education is education to purpose for children maturation be come human be autonomous, responsible and be able to problem solving your live alone. Education must directed in place where children in a place. Curriculum that used every subject does not can separated but constitute unit integrated, and experience in the school always integrated with experience outside school. That Problems appointed by teacher in classroom is actual problems attractive that interest for children or to become center of notice for children. That application of method by teacher is diciplin method but authorization. All subject matter that in display must be basic facts that in observed, understanded, along with previously discussed and subject matters talked about probabled contains ideas that can develop situation for achieve to purpose. Teacher role in pragmatic education but of as facilitator and motivator children activity. All children activity carry out self in a row with interest and necessary that chooised, but teacher permanent supply directive that enable children to growth appropriate with talent and that possessed interest.